Posteromedial Approach in Treatment of Talar Posterior Process Fractures. (1st August 2013) - Shi, Zhongmin; Zou, Jian; Yi, Xincheng
ABSTRACT: To evaluate the surgical outcomes of talar, posterior process displaced fractures with posteromedial approach. From January 2008 to December 2010, 18 patients with displaced fracture of talar posterior process were treated in our department. Open reduction and screw fixation through posteromedial approach was performed after soft tissue swelling were subsided. The results were evaluated with Visual Analog Scale Pain Score (VAS) and American Orthopedic Foot and Ankle Society (AOFAS) scores. The average follow-up period was 16.8 months. There was no wound infection or nerve injury. There was no screw loosening, implant breakage, nonunion, or malunion. The average AOFAS score was 83.1, and the VAS score was 1.4. Two patients developed posttraumatic subtalar joint arthritis 1 year after operation, and one of them had subtalar arthrodesis performed due to pain and walking disability. Posteromedial approach can provide a good surgical exposure to the posterior portion of the talus without compromising the surrounding neurovascular structures. Small fragment screws can provide stable fixation and early mobilization of the ankle and subtalar joint. Open reduction and internal fixation via posteromedial approach is an effective and reliable method for the treatment to displaced fractures of the posterior process of the talus.